2014
DOI: 10.1111/age.12197
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium over short physical distances measured in sheep using a high‐density SNP chip

Abstract: The extent of linkage disequilibrium (LD) between genetic loci has implications for both association studies and the accuracy of genomic prediction. To characterise the persistence of LD in diverse sheep breeds, two SNP genotyping platforms were used. First, existing SNP genotypes from 63 breeds obtained using the ovine SNP50 BeadChip (49,034 loci) were used to estimate LD decay in populations with contrasting levels of genetic diversity. Given the paucity of marker pairs separated by short physical distances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
89
4
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 25 publications
21
89
4
2
Order By: Relevance
“…These studies of LD in dairy sheep breeds showed lower values than those seen for Barbaresca, indicating that LD decay was breed-specific. Recently, Kijas et al (2014), in a study of five sheep breeds that used a high-density SNP chip, found an average r 2 ranging from 0.080 to 0.224 for SNPs up to 70 kb apart and reported that LD decayed faster and at a much shorter genomic distance. Consistent with our results, Al-Mamun et al (2015) reported that the maximum average LD was located between adjacent SNPs on OAR10 and a higher average LD was seen in meat sheep breeds.…”
Section: Discussionmentioning
confidence: 99%
“…These studies of LD in dairy sheep breeds showed lower values than those seen for Barbaresca, indicating that LD decay was breed-specific. Recently, Kijas et al (2014), in a study of five sheep breeds that used a high-density SNP chip, found an average r 2 ranging from 0.080 to 0.224 for SNPs up to 70 kb apart and reported that LD decayed faster and at a much shorter genomic distance. Consistent with our results, Al-Mamun et al (2015) reported that the maximum average LD was located between adjacent SNPs on OAR10 and a higher average LD was seen in meat sheep breeds.…”
Section: Discussionmentioning
confidence: 99%
“…The moderate MAF levels demonstrate the great genetic diversity of this population. However, these values can even be underestimated, because in the development of the HD SNP chip, a proportion of SNP with low MAF were included [6]. From the 517,902 SNPs that passed quality control, 82,859 (16%) of the SNPs had MAF less than or equal to 0.10.…”
Section: Discussionmentioning
confidence: 99%
“…In a LD study including a collection of 74 sheep breeds and 49,034 SNP, Kijas et al [23] observed a high variation in LD levels among breeds, with a Scottish breed (Soay) presenting the highest levels of LD and Qezel sheep (sampled in Iran) the lowest levels of LD. Using the HD SNP chip, Kijas et al [6] reported LD levels at 10 kb of 0.186, 0.191, 0.279, 0.221 and 0.339 for Merino ewes, Merino sires, Poll Dorset, Suffolk and Border Leicester, respectively. For the population investigated in this study the LD levels at 10 kb were 0.179, smaller than estimates by Kijas et al [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although highly informative, the current panels of microsatellites used for analyses are not capable of elucidating all the information required regarding breed variation in livestock (Toro et al, 2009). Recently, it is becoming more evident that SNP analysis is more suited for the high throughput genotyping that is required to elucidate greater molecular insights such as historical signatures of selection (Qanbari, Pausch, Jansen et al, 2014), phenotypic variations within livestock breeds (Groenen, Megens, Zare et al, 2011) as well as linkage disequilibrium over short physical distances (Kijas, Porto-Neto, Dominik et al, 2014) than any of the other molecular markers currently available. The availability and accessibility of comprehensive databases of genomic data for various uses has also facilitated population genetic studies globally for example; the National Centre for Biotechnology Information(NCBI) (Sayers, Barrett, Benson et al, 2011), Livestock Animal Quantitative Trait Loci (QTL) database (Hu, Park, Wu et al, 2013), and University of California Santa Cruz (UCSC) genome browser (Dreszer, Karolchik, Zweig et al, 2012).…”
Section: Modelling: the Way Forwardmentioning
confidence: 99%